Value Chain Mapping Value Chain Mapping Based on Deep Learning in Cyber Security for Sustainability Development Smart Bandung City: Value Chain Mapping Based on Deep Learning in Cyber Security for Sustainability Development Smart Bandung City - Wijaya, Rahmadi; Rosmiati, Mia; Hidayati, Hetti (PPM Telkom University, 2024)
Smart City is a lifestyle of people who use computers or electronic media to make their information needs easier. Through digitalization, everyone can get a more efficient, controllable, economical, productive, integrated, and sustainable life. However, to get this progress, a model for developing smart city initiatives is needed and becomes a chain so that it can continue to be developed in the context of a smart city. Therefore, to develop global smart city technologies, a smart city must create a Value Chain Mapping (VCM). This paper aims to map the layers program with the currently running value chain mapping for smart city sustainable development. For this purpose, this research focused on the use of value chain mapping based on security services on smart city components: the environment and lifestyle, mobility, and health. Furthermore, deep learning methods as well as technology correlation in a smart city are explained. Mapping an environmental program layer using Deep Learning in Cyber Security services could prevent vulnerabilities that occur when implementing information technology